Antifungal, Antioxidant and Antibiofilm Activities of Essential Oils of Cymbopogon spp. - Wafa Rhimi; Mona A. Mohammed; Aya Attia Koraney Zarea; Grazia Greco; Maria Tempesta; Domenico Otranto; Claudia Cafarchia (MDPI AG, 2022)
Essential oils (EOs) of Cymbopogon citratus and Cymbopogon proximus are known as sources of monoterpenes and sesquiterpenoids, although their biological activities have not been well investigated. In this study, the compositions of C. citratus and C. proximus EOs of Egyptian origin and their antifungal and antibiofilm properties against Candida spp. and Malassezia furfur were investigated. Antioxidant activities were also evaluated. GC-MS showed the presence of nine and eight constituents in C. citratus and C. proximus EOs, respectively, with geranial and neral as the major compounds of C. citratus EO and piperitone and α-terpinolene as the major compounds of C. proximus EO. Both EOs showed antifungal (MIC values ranging from 1.25 to 20 µL/ mL) and antibiofilm activities (% of reduction ranging from 27.65 ± 11.7 to 96.39 ± 2.8) against all yeast species. The antifungal and antibiofilm activities of C. citratus EO were significantly higher than those observed for C. proximus EO. M. furfur was more susceptible to both EOs than Candida spp. Both EOs exhibited the highest antioxidant activity. This study suggests that C. citratus and C. proximus EOs might be an excellent source of antifungal, antibiofilm and antioxidant drugs and might be useful for preventing Malassezia infections in both medical and veterinary medicine.